A framework to internationalise South African small and medium enterprises through the Africa Continental Free Trade Agreement - Nakani, Akona (Graduate School of Business (GSB), 2026)
This research investigates the use of the African Continental Free Trade Agreement to provide a complete framework for promoting the internationalisation of South African Small and Medium Enterprises. The African Continental Free Trade Agreement was established in 2012 and is one of the largest free trade areas in the world in terms of the number of participating countries and it became operational in January 2021. It offers significant prospects for Small and Medium Enterprises by reducing trade barriers, establishing a cohesive market among 54 African countries, and promoting intra-African trade. The research uses a qualitative research approach and semi-structured interviews to collect data from Small and Medium Enterprises that have benefited from the Department of Trade, Industry and Competition's Export Marketing and Investment Assistance incentive scheme, as well as the Department of Trade, Industry and Competition personnel responsible for export development and international trade. The data collected was qualitative, therefore, the researcher utilised thematic analysis, a method that specifically aims to identify, structure, and analyse themes within textual material. The study findings provide insight into a wide range of factors that influence internationalisation such as; barriers to market entry, financial constraints, lack of support mechanisms for Small and Medium Enterprises, collaborative networks for export growth, African Continental Free Trade Agreement as an enabler, access to market information, trade data as well as adapting to local conditions. This study is anticipated to be highly informative and impactful, addressing critical needs and offering substantial benefits to various stakeholders such as Small and Medium Enterprises, policymakers, and trade facilitators. Its significance lies in its potential to transform the landscape of Small and Medium Enterprises internationalisation in South Africa. The results demonstrated a dynamic landscape shaped by regulatory complexities, financial constraints, the potential of the African Continental Free Trade Agreement as a unifying market, and the critical role of support systems and adaptive strategies for successful Small and Medium Enterprise internationalisation. The study offers several recommendations, including prioritising harmonizing of regulatory standards across the continent, access to Small and Medium Enterprise-focused trade finance, improving logistics and trade infrastructure, institutional support and capacity building, and collaboration through trade shows. Future research should be on Sector Specific Regulations pertaining to South African Small and Medium Enterprises on African regional trade.